A Practical and Efficient Blockchain-Assisted Attribute-Based Encryption Scheme for Access Control and Data Sharing. (30th September 2022) - Hong, Linjian; Zhang, Kai; Gong, Junqing; Qian, Haifeng
Abstract : Attribute-based encryption (ABE) is a powerful encryption scheme with flexible access control over encrypted data that has been widely adopted in cloud computing scenarios to facilitate data sharing. However, despite convenience and efficiency provided by data sharing based on cloud, it is commonly vulnerable to issues like key abuse (namely, illegal key sharing by user or key distribution by authority) and key escrow (namely, illegal decryption by ABE authority). Hence, exploring a more secure ABE scheme that can be key abuse and key escrow resistant is crucial. Furthermore, data modification that happens in cloud storage and outsourced computation is also a challenge for the cloud-based data sharing schemes. To handle the above issues, in this paper, we propose a secure and efficient data sharing scheme based on attribute-based encryption (ABE) and blockchain equipped with InterPlanetary File System (IPFS). In particular, we show that the large-universe ABE with outsourced decryption (LU-ABE-OD) scheme proposed by Ning et al. is vulnerable to key escrow attack, which is not secure enough in the data sharing scenario. Therefore, based on their basic proposal, we construct an improved multi-authority LU-ABE-OD scheme to encrypt personal data, which are stored in the IPFS system while blockchain is applied to store the hash value returned by IPFS and be responsible for the outsourced decryption. As a result, our scheme greatly reduces the decryption overheads of the user while risks of key abuse and key escrow can be settled. Meanwhile, the introduction of IPFS significantly reduces the storage burden on chain without data tampering problem. Through theoretical analysis and experimental simulation, we prove the feasibility, security, and efficiency of our scheme.